Multi-objective ship path planning using non-dominant relationship-based WOA in marine meteorological environment. (15th December 2022) - Han, Qilong; Yang, Xiao; Song, Hongtao; Du, Wei
Abstract: Marine environmental issues have become increasingly prominent in recent years, and ocean transportation has also received extensive attention. Relevant personnel is concerned about the minimum fuel consumption and the shortest sailing time, which are two contradictory goals. This paper describes the ship path problem model as a multi-objective optimization model considering fuel consumption and navigation time. The waves, wind speed, and wind direction in the marine meteorological environment significantly impact the ship's actual navigation, making it challenging to design a reasonable path. Ship path planning in the marine environment is an NP-Hard Problem. The paper applies an improved whale optimization algorithm to find Pareto solutions in the multi-objective optimization model considering marine meteorology. This paper discusses the performance of the enhanced algorithm. Compared with other advanced algorithms, the algorithm is applied to five benchmark multi-objective optimization functions. The test results show that the scheme can balance the ship's fuel consumption and sailing time to provide a reasonable candidate path for decision-makers. Highlights: This paper describes the ship path problem model as a multi-objective ship path optimization model considering fuel consumption and navigation time. The improved whale optimization algorithm solves the multi-objective optimization problem. Non-dominated relations determine the solution to multi-objective problems. Ship path planning considers the influence of ship parameters and marine meteorological data.